Role of Special Economic Zone in Development: Status of Nepal - Khatiwada, Yam Kumari (Prashasan: The Nepalese Journal of Public Administration, 2022)
Nepal initiated the concept of Special Economic Zone (SEZ) since 1980s. However, the process of construction of infrastructure development and operation of such zone is very slow. Now there is only one SEZ is in operation partially and one is ready for operation. SEZ can play an important role to uplift the economic condition of Nepal as it is in the process of graduating to developing country from least developed countries (LDCs) in near future and meeting the 2030 agendas of SDGs. Investment in productive sector increase the production and productivity that leads towards the import substitution and export promotion. To attract both foreign and domestic investment SEZ is an important mechanism. This article has focused on how the role of economic zone can be enhanced in development of Nepal. It has identified some challenges to be addressed and the opportunities that need to be grasped. Based on the analysis of the status of SEZ in Nepal this study has recommended some areas of reforms for effective operation of on-going SEZ and upcoming SEZ in Nepal. Reforms of existing legal, institutional and procedures mechanism related to SEZ are required to create conducive environment to attract domestic, foreign and multinational companies inside the zone. Adequate research and development on the sector of comparative advantage and competitiveness is necessary and at the same time, public private dialogue and international networking in this regard is also equally important.